Implementasi Rancangan Pelatihan Kemetrologian bagi Juru Timbang Menggunakan Metode ADDIE : Studi Kasus : Bandung Raya - Harfiah, Rismisari (Pusat Pengembangan Kompetensi Aparatur Perdagangan, 2019)
Legal metrology is a very large and complex field to be implemented. In realizing orderly measurement for all of Indonesia, very large human resources are needed. A total of 1900 Metrology Human Resources currently available cannot meet the needs of the community, which includes at least 14.230 traditional markets and hundreds of modern markets spread throughout Indonesia. Adding large numbers of Metrologi personnel from ASN is very difficult, the most likely choice is to recruit personnel outside metrology such as market managers of traditional and modern market. This situation encouraging idea to recruit weighers whose task is to check the scales in traditional and modern markets. Through the ADDIE method which include analize, design, develop, implementation and evaluation a training model for weighers is designed. As a result, two days of training (20 JP) with classroom learning methods and laboratory practices is held . Furthermore, the weigher conducts trials in the market where each of them is on duty. The evaluation results with an average value of 4.43 of 5 Likert Scale indicate that the training is satisfying and meets the needs of the knowledge and skills of the weighers before duty.